The Effects Of Erythritol Intake On Cardiovascular Health: A Review - Rebecca Djohari, Cathleen; Theodora Pratiknyoadi, Denita; Simajaya, Jane; Andrea Setiawan, Janice; Frans Putri, Kimberly; Setya Aritonang, Martha (Green Publisher Indonesia, 2024)
A popular low-calorie sweetener is erythritol, a naturally occurring sugar alcohol that can be found in fruits and fermented foods. Due to its lower calorie content, it has become a popular replacement for sugar, particularly for those who have diabetes. Although erythritol is believed to be safe for the majority of individuals, current research indicates that it may be linked to cardiovascular diseases, including a higher risk of blood clots formation, heart attack, and stroke. This paper discusses the erythritol's natural occurrence, production, and metabolism while raising concerns about its potential effects on human health.